2021
DOI: 10.3399/bjgp.2021.0446
|View full text |Cite
|
Sign up to set email alerts
|

Role of GPs in shared decision making with patients about palliative cancer treatment: a qualitative study in the Netherlands

Abstract: Background: General practitioners (GPs) are well-positioned to enhance shared decision-making (SDM) about treatment for patients with advanced cancer. However, to date, little is known about GPs’ views on their contribution to SDM. Aim: To explore GPs’ perspectives on their role in SDM about palliative cancer treatment and the preconditions to fulfil this role. Design and setting: Qualitative interview study among Dutch GPs. Method: GPs were sampled purposefully and conveniently. In-depth semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…53 Besides oncologists, nurses and general practitioners can support SDM by deliberating patients' goals during the illness trajectory. 82,83 Addressing patients' coping style and emotions may additionally help to actualize high-quality, goal-concordant care throughout the last phase of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Besides oncologists, nurses and general practitioners can support SDM by deliberating patients' goals during the illness trajectory. 82,83 Addressing patients' coping style and emotions may additionally help to actualize high-quality, goal-concordant care throughout the last phase of life.…”
Section: Discussionmentioning
confidence: 99%
“…53 Besides oncologists, nurses and general practitioners can support SDM by deliberating patients' goals during the illness trajectory. 82,83 Addressing patients' coping style and emotions may additionally help to actualize high-quality, goalconcordant care throughout the last phase of life. We used mixed linear modeling with two levels, since inclusion of a third level (oncologists) did not improve model fit and the ICC was low (ICC LL 5 0.00).…”
Section: Jco Oncology Practice E1821mentioning
confidence: 99%
“…42,48,57,58 Some of the included studies showed that being involved in early decision-making about palliative treatment could build a relationship for future end-of-life discussions, and, as situations changed, physicians and nurses revisited previous information and engaged with people with cancer and their families to reflect on the current situation. 53,[58][59][60] Also, with limited expected benefit of treatment, more room was given to considerations of patients' preferences, as De Snoo-Trimp et al 44…”
Section: Clearly State (P 168)mentioning
confidence: 99%
“…Firstly, they may motivate and promote patient involvement, and create awareness of choice. 43,58,60,61 As above, perceptions and awareness of equal choices can be limited, but one study 60,61 found that nurses can enable this. Bos-van den Hoek et al 61…”
Section: One Patient Said: It Is Difficult For Me To Choose Because Y...mentioning
confidence: 99%
See 1 more Smart Citation